Infection strategies of enteric pathogenic Escherichia coli - Clements, Abigail (Landes Bioscience, 2012)
Enteric Escherichia coli (E. coli) are both natural flora of humans and important pathogens causing significant morbidity and mortality worldwide. Traditionally enteric E. coli have been divided into 6 pathotypes, with further pathotypes often proposed. In this review we suggest expansion of the enteric E. coli into 8 pathotypes to include the emerging pathotypes of adherent invasive E. coli (AIEC) and Shiga-toxin producing enteroaggregative E. coli (STEAEC). The molecular mechanisms that allow enteric E. coli to colonize and cause disease in the human host are examined and for two of the pathotypes that express a type 3 secretion system (T3SS) we discuss the complex interplay between translocated effectors and manipulation of host cell signaling pathways that occurs during infection.